The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1088/1478-3975/aac193
|View full text |Cite
|
Sign up to set email alerts
|

Insight into nuclear body formation of phytochromes through stochastic modelling and experiment

Abstract: Spatial relocalization of proteins is crucial for the correct functioning of living cells. An interesting example of spatial ordering is the light-induced clustering of plant photoreceptor proteins. Upon irradiation by white or red light, the red light-active phytochrome, phytochrome B, enters the nucleus and accumulates in large nuclear bodies (NBs). The underlying physical process of nuclear body formation remains unclear, but phytochrome B is thought to coagulate via a simple protein-protein binding process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The structural basis of the light-dependent PB localization of phyB has been extensively investigated. PhyB is a homodimer; PB localization requires the dimeric Pfr form of phyB 40,41,43,46,59 . Each phyB monomer contains an N-terminal photosensory module and a C-terminal output module 20,21 .…”
Section: Resultsmentioning
confidence: 99%
“…The structural basis of the light-dependent PB localization of phyB has been extensively investigated. PhyB is a homodimer; PB localization requires the dimeric Pfr form of phyB 40,41,43,46,59 . Each phyB monomer contains an N-terminal photosensory module and a C-terminal output module 20,21 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they reasoned that photobody formation consists of two steps: a fast nucleation step in which phyB aggregates or binds to other proteins, followed by a slower step of more complex binding. Grima et al (2018) also suggested that photobodies may be hollow, which has since been supported by microscopy evidence (Perrella et al, 2021). In this case, phyB may bind to a structural component, also referred to as a seed component, to initiate formation (Mao et al, 2011;Shevtsov and Dundr, 2011; Figure 2).…”
Section: Photobody Biogenesismentioning
confidence: 80%
“…Once these multivalent molecules reach a local concentration above the threshold level, they assemble into complex polymers and undergo LLPS to promote body formation (Sawyer, Hager, & Dundr, ). Recent modeling of plant phytochrome MLO formation suggests this is a two‐step process, consisting of an initial rapid macroparticle formation step and slow macroparticle aggregation into mature droplets (Grima et al, ). These MLO condensates are structurally stable but their protein and RNA constituents exchange dynamically with the surrounding nucleoplasm.…”
Section: Cellular Spatial Organization Depends On Biological Self‐orgmentioning
confidence: 99%